A non-expensive bidimensional kinematic balance assessment can detect early postural instability in people with Parkinson’s disease - Santos, Gabriel Venas; d'Alencar, Matheus Silva; Helene, Andre Frazão; Roque, Antonio C.; Miranda, José Garcia Vivas; Piemonte, Maria Elisa Pimentel (Frontiers in Neurology, 2023)
Background Postural instability is a debilitating cardinal symptom of Parkinson’s disease (PD). Its onset marks a pivotal milestone in PD when balance impairment results in disability in many activities of daily living. Early detection of postural instability by non-expensive tools that can be widely used in clinical practice is a key factor in the prevention of falls in widespread population and their negative consequences. Objective This study aimed to investigate the effectiveness of a two-dimensional balance assessment to identify the decline in postural control associated with PD progression. Methods This study recruited 55 people with PD, of which 37 were men. Eleven participants were in stage I, twenty-three in stage II, and twenty-one in stage III. According to the Hoehn and Yahr (H&Y) rating scale, three clinical balance tests (Timed Up and Go test, Balance Evaluation Systems Test, and Push and Release test) were carried out in addition to a static stance test recorded by a two-dimensional movement analysis software. Based on kinematic variables generated by the software, a Postural Instability Index (PII) was created, allowing a comparison between its results and those obtained by clinical tests. Results There were differences between sociodemographic variables directly related to PD evolution. Although all tests were correlated with H&Y stages, only the PII was able to differentiate the first three stages of disease evolution (H&Y I and II: p = 0.03; H&Y I and III: p = 0.00001; H&Y II and III: p = 0.02). Other clinical tests were able to differentiate only people in the moderate PD stage (H&Y III). Conclusion Based on the PII index, it was possible to differentiate the postural control decline among the first three stages of PD evolution. This study offers a promising possibility of a low-cost, early identification of subtle changes in postural control in people with PD in clinical practice.